KLINIK BISNIS MOBILE TERPADU DALAM MENDORONG PENGUATAN PASAR SEKTOR LAPAK JAJANAN PASAR PADA MASA KEBIASAAN BARU - Sri Suwarsi,; Kiki Zakiah,; Rusman Frendika,; Azib Asro i,; Isniar Budiarti, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
There are currently 13 micro-enterprises in the snack market sector in the city of Bandung which have been collected based on observations, video calls with several stall owners, discussions with booth showcase design designers, and interviews with (ASPAMI (Association of Indonesian Food and Beverage Entrepreneurs) and also the results of discussions in the FGD (forum group discussion) between the Unisba PKM (Community Service) team and the Bandung Kadin to strengthen the portrait of this business problem phenomenon and try to provide the right solution to the problem. booth or showcase as an attractive place for selling, increasing online marketing, providing marketable packaging tutorials, and initiating the formation of a cooperative for street food stalls. These efforts have yielded positive results, although they are still not optimal during the adaptation period of this new habit, but they are available. Yes, attractive booths and the use of social media such as Whatsapp, Facebook, and Instagram as promotional media have been successfully realized, by developing both the appearance of photo designs, writing or narration and the promotional content displayed.